Riggs family papers - Riggs, Elisha, 1779-1853.; Riggs, Elisha, 1826-1881.; Riggs, Elisha Francis, 1851-1910.; Riggs, Elisha Francis, 1887-1936.; Riggs, George Washington, 1813-1881.; Riggs, Romulus, 1782-1846.; Riggs, Thomas, 1873-1945.; Riggs, T. Lawrason (Thomas Lawrason), 1888-1943.; Riggs, William Henry, 1837-1924.
Family and business correspondence, diaries, writings, financial records, biographical and genealogical papers, printed matter, and other papers of Riggs family members.
Includes papers of Elisha Riggs (1779-1853) relating to family affairs, travel in Europe, sales of land in Illinois, and the development of his New York mercantile business; papers of Elisha Riggs, Jr. (1826-1881) relating to travel in Great Britain, the firm of Corcoran & Riggs, and the Averill Coal and Oil Company, West Va.; papers of Elisha Francis Riggs (1851-1910); papers of Elisha Francis Riggs, Jr. (1887-1936) relating to family matters, military service at Fort Riley, Kan., and in the Philippines, and diplomatic service in Russia during the Russian Revolution; papers of George Washington Riggs relating, in part, to Corcoran & Riggs; and papers of Romulus Riggs.
Also includes the papers of Thomas Riggs, Jr., relating to gold mining in Alaska, the Alaskan Engineering Commission, his governorship of Alaska, the Alaska Boundary Survey, and to family matters; papers of T. Lawrason Riggs relating to personal and family matters, World War I service with the U.S. Army American Expeditionary Forces in France, experiences as a Catholic priest, and writings; and papers of William Henry Riggs relating to his travels in Egypt, Palestine, Spain, and Syria, and to his interests in the art world, including his donations to the Metropolitan Museum of Art. Includes papers of other family members and records of the firm of Corcoran & Riggs relating, in part, to the financing of the Mexican War and the settlement (1843) of Choctaw and Chickasaw land claims.
Correspondents include George Bancroft, Clara Barton, Thomas Hart Benton, Albert Bierstadt, Dion Boucicault, James Buchanan, Ole Bull, John C. Calhoun, George Earle Chamberlain, Walter Eli Clark, Grover Cleveland, W.W. Corcoran, Frederic R. Coudert, Frederick S. Cozzens, J.L.M. Curry, Jefferson Davis, John W. Davis, John Elliott, Ernest Gruening, Joseph F. Guffey, Nathan Hale, Franklin K. Lane, Francis Napier, George Newbold, Noel J. Ogilvie, John Howard Payne, George Peabody, James K. Polk, William Henry Seward, John Slidell, Buckingham Smith, Julian Street, Booth Tarkington, Daniel Webster, Levi Woodbury, and Brigham Young.
Microfilm edition of Thomas Riggs, Jr., memoirs available
Microfilm edition of Thomas Lawrason Riggs diaries available
Microfilm produced from originals in Manuscript Division.
Microfilm of selected letters (Microfilm 6,124A-1N-1P) produced from originals in private hands.
Library of Congress Prints and Photographs Division.
Library of Congress Geography and Map Division.
Keywords: Bancroft, George, -- 1800-1891 -- Correspondence; Barton, Clara, -- 1821-1912 -- Correspondence; Benton, Thomas Hart, -- 1782-1858 -- Correspondence; Bierstadt, Albert, -- 1830-1902 -- Correspondence; Boucicault, Dion, -- 1820-1890 -- Correspondence; Buchanan, James, -- 1791-1868 -- Correspondence; Bull, Ole, -- 1810-1880 -- Correspondence; Calhoun, John C. -- 1782-1850 -- Correspondence; Chamberlain, George E. -- 1854-1928 -- Correspondence; Clark, Walter Eli, -- 1869-1950 -- Correspondence; Cleveland, Grover, -- 1837-1908 -- Correspondence; Corcoran, W. W. -- 1798-1888 -- Correspondence; Coudert, Frederic R. -- 1871-1955 -- Correspondence; Cozzens, Frederic S. -- 1818-1869 -- Correspondence; Curry, J. L. M. -- 1825-1903 -- Correspondence; Davis, Jefferson, -- 1808-1889 -- Correspondence; Davis, John W. -- 1873-1955 -- Correspondence; Elliott, John, -- active 1841-1889 -- Correspondence; Gruening, Ernest, -- 1887-1974 -- Correspondence; Guffey, Joseph F., -- 1870-1959 -- Correspondence; Hale, Nathan, -- 1784-1863 -- Correspondence; Lane, Franklin K. -- Correspondence; Napier, Francis, -- Baron Napier and Ettrick, -- 1819-1898 -- Correspondence; Newbold, George -- Correspondence; Ogilvie, Noel J. -- Correspondence; Payne, John Howard, -- 1791-1852 -- Correspondence; Peabody, George, -- 1795-1869 -- Correspondence; Polk, James K. -- 1795-1849 -- Correspondence; Seward, William Henry, -- 1801-1872 -- Correspondence; Slidell, John, -- 1793-1871 -- Correspondence; Smith, Buckingham, -- 1810-1871 -- Correspondence; Street, Julian, -- 1879-1947 -- Correspondence; Tarkington, Booth, -- 1869-1946 -- Correspondence; Webster, Daniel, -- 1782-1852 -- Correspondence; Woodbury, Levi, -- 1789-1851 -- Correspondence; Young, Brigham, -- 1801-1877 -- Correspondence; Riggs family; United States. -- Army; United States. -- Army. -- American Expeditionary Forces; Alaskan Boundary Survey; Alaskan Engineering Commission; Averill Coal and Oil Company; Corcoran & Riggs; Metropolitan Museum of Art (New York, N.Y.); Art; Banks and banking -- Washington (D.C.); Catholic Church -- Clergy; Chickasaw Indians -- Claims; Choctaw Indians -- Claims; Coal mines and mining -- West Virginia; Diplomatic and consular service, American -- Soviet Union; Gold mines and mining -- Alaska; Indians of North America -- Land tenure; Merchants -- New York (State) -- New York; Mexican War, 1846-1848 -- Finance; Military bases -- Kansas; Military bases, American -- Philippines; Surveying -- Alaska; World War, 1914-1918 -- France; Alaska -- Politics and government